vector-valued singular integrals and maximal functions on spaces of homogeneous type - Grafakos, Loukas; Liu, Liguang; Yang, Dachun (MATHEMATICA SCANDINAVICA, 2009)
The Fefferman-Stein vector-valued maximal function inequality is proved for spaces of homogeneous type. The approach taken here is based on the theory of vector-valued Calderón-Zygmund singular integral theory in this context, which is appropriately developed.